Development of a model for the integrated management of the international delivery chains formation - Khalipova, Nataliya; Bosov, Arkadii; Prohoniuk, Iryna (Eastern-European Journal of Enterprise Technologies, 2018)
We propose a model for the formation of international logistics chains based on an integrated multicriterial analysis of potential cargo transportation routes and delivery cost. The application of the systemic approach when planning a delivery helps to ensure rational allocation and efficient servicing of traffic flows among the objects along the transportation-logistic network. At the first stage of modeling, the analysis of information about the objects of the transport and logistic system is carried out. We determine the region of efficient use of different modes of transport and construct a set of alternative chains of good delivery. Based on the analysis of the impact factors, the criteria are determined and the constraints are accepted to a given problem for a series of techno-economic, logistical, technological, environmental and other indicators. At the second stage, the multicriterial problem of synthesis (engineering) of the transport and logistics system of delivery is solved. We built an algorithm for the substantiation of effective international multi-modal transport and technological schemes of cargo delivery. The proposed algorithm provides a comprehensive assessment of the cost depending on delivery conditions in accordance with the Incoterms rules and the customs regime. To substantiate the route, the region of effective solutions for a DM is determined, based on solving a problem on the vector optimization for multiple criteria. Formation of effective schemes of cargo delivery from France to Ukraine along the route from Haut-Mauco to the warehouse "Agro-Soyuz-Terminal" in the city of Dnipro was explored. Based on modeling applying the package of symbolic computations in the programming environment Maple-7, we obtained a full set of compromise solutions to the vector optimization problem for the criteria of cost, delivery time, and ecological impact. We present a comprehensive assessment of the cost of goods delivery in containers using mixed transportation under the Incoterms EXW, CPT delivery conditions (delivery to Dnipro), FOB and CIF, and the customs regime of import and import (warehouse). The proposed model could be applied by transportation, logistic, customs brokering companies when substantiating alternative routes of goods delivery based on a multicriterial analysis of information.